Silk from Crickets: A New Twist on Spinning - Walker, Andrew A.; Weisman, Sarah; Church, Jeffrey S.; Merritt, David J.; Mudie, Stephen T.; Sutherland, Tara D. (PLOS ONE, 2012)
Raspy crickets (Orthoptera: Gryllacrididae) are unique among the orthopterans in producing silk, which is used to build shelters. This work studied the material composition and the fabrication of cricket silk for the first time. We examined silk-webs produced in captivity, which comprised cylindrical fibers and flat films. Spectra obtained from micro-Raman experiments indicated that the silk is composed of protein, primarily in a beta-sheet conformation, and that fibers and films are almost identical in terms of amino acid composition and secondary structure. The primary sequences of four silk proteins were identified through a mass spectrometry/cDNA library approach. The most abundant silk protein was large in size (300 and 220 kDa variants), rich in alanine, glycine and serine, and contained repetitive sequence motifs; these are features which are shared with several known beta-sheet forming silk proteins. Convergent evolution at the molecular level contrasts with development by crickets of a novel mechanism for silk fabrication. After secretion of cricket silk proteins by the labial glands they are fabricated into mature silk by the labium-hypopharynx, which is modified to allow the controlled formation of either fibers or films. Protein folding into beta-sheet structure during silk fabrication is not driven by shear forces, as is reported for other silks.